Measuring the α-particle charge radius with muonic helium-4 ions - Krauth, Julian J. (2022)
This work was performed at HIPA at PSI. We thank the accelerator and beamline support groups for excellent conditions. We also thank L. Simons, U. Roser, M. Nussli, H. v. Gunten, B. Zehr, W. Lustermann, A. Gendotti, A. Muller, F. Barchetti, B. van den Brandt, P. Schurter, M. Horisberger, A. Weber, S. Spielmann-Jaggi, U. Greuter, P.-R. Kettle, S. Ritt, W. Simons, K. Linner, H. Bruckner, K. S. E. Eikema and the PSI, ETH and MPQ workshops and support groups for their help. We acknowledge the support of the following grants: European Research Council (ERC) through StG. 279765 and CoG. 725039, Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany's Excellence Initiative EXC 1098 PRISMA (194673446) and Excellence Strategy EXC PRISMA+ (390831469), DFG_GR_3172/9-1, MOST of Taiwan under contract number 106-2112-M-007 -021 -MY3, Fundacao para a Ciencia e a Tecnologia (FCT), Portugal, and FEDER through COMPETE in the framework of project, PEstOE/FIS/UI0303/2011,and UID/04559/2020 (LIBPhys), contract numbers , SFRH/BD/52332/2013, and by SNF 200021L_138175, SNF 200020_159755 and SNF 200021_165854, as well as the ETH-FAST initiative as part of the NCCR MUST programme.